TGM4: an immunogenic prostate-restricted antigen. Issue 6 (30th June 2021) - Lopez-Bujanda, Zoila A; Obradovic, Aleksandar; Nirschl, Thomas R; Crowley, Laura; Macedo, Rodney; Papachristodoulou, Alexandros; O'Donnell, Timothy; Laserson, Uri; Zarif, Jelani C; Reshef, Ran; Yuan, Tiezheng; Soni, Mithil K; et al.
Abstract : Background: Prostate cancer is the second leading cause of cancer-related death in men in the USA; death occurs when patients progress to metastatic castration-resistant prostate cancer (CRPC). Although immunotherapy with the Food and Drug Administration‐approved vaccine sipuleucel‐T, which targets prostatic acid phosphatase (PAP), extends survival for 2–4 months, the identification of new immunogenic tumor-associated antigens (TAAs) continues to be an unmet need. Methods: We evaluated the differential expression profile of castration-resistant prostate epithelial cells that give rise to CRPC from mice following an androgen deprivation/repletion cycle. The expression levels of a set of androgen-responsive genes were further evaluated in prostate, brain, colon, liver, lung, skin, kidney, and salivary gland from murine and human databases. The expression of a novel prostate-restricted TAA was then validated by immunostaining of mouse tissues and analyzed in primary tumors across all human cancer types in The Cancer Genome Atlas. Finally, the immunogenicity of this TAA was evaluated in vitro and in vivo using autologous coculture assays with cells from healthy donors as well as by measuring antigen-specific antibodies in sera from patients with prostate cancer (PCa) from a neoadjuvant clinical trial. Results: We identified a set of androgen-responsive genes that could serve as potential TAAs for PCa. In particular, we found transglutaminase 4 (Tgm4) to be highly expressed in prostate tumors that originate from luminal epithelial cells and only expressed at low levels in most extraprostatic tissues evaluated. Furthermore, elevated levels of TGM4 expression in primary PCa tumors correlated with unfavorable prognosis in patients. In vitro and in vivo assays confirmed the immunogenicity of TGM4. We found that activated proinflammatory effector memory CD8 and CD4 T cells were expanded by monocyte-derived dendritic cell (moDCs) pulsed with TGM4 to a greater extent than moDCs pulsed with either PAP or prostate-specific antigen (PSA), and T cells primed with TGM4-pulsed moDCs produce functional cytokines following a prime/boost regiment or in vitro stimulation. An IgG antibody response to TGM4 was detected in 30% of vaccinated patients, while fewer than 8% of vaccinated patients developed antibody responses to PSA or prostate-specific membrane antigen (PSMA). Conclusions: These results suggest that TGM4 is an immunogenic, prostate-restricted antigen with the potential for further development as an immunotherapy target.